Thank you for the opportunity to help you with your question!

ln(e²x^5 / (x+2)^(1/3)) = ln(e²x^5) - ln((x+2)^(1/3)) because ln(a/b) = ln(a) - ln(b)

= ln(e²) + ln(x^5) - (1/3)ln(x + 2) because ln(a*b) = ln(a) + ln(b)

= 2 + 5ln(x) - (1/3)ln(x + 2) because ln(a^b) = bln(a) and ln(e^x) = x

if you don't understand something just ask

Each time you have any other question or homework just invite me i will give you the best answer ok

Good Luck

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up